Análisis de mercado de los medios de prensa escrita de la ciudad de Machala - Rambay Vargas, Tania Gissella (2015)
This integration project aims to make a plan of marketing mix for acquisition and retention of new consumers by segmenting the market newspapers (newspaper) in the city of Machala, was used for the collection of technical information obtained from the survey Quantitative data was applied to 398 inhabitants of this city, of which information concerning the acceptance they have the three most important newspapers in the city of Machala was sought are: Daily Review, The Mail and National. We study the consumer behavior of the inhabitants of the city of Machala, in the consumption of print media and identify the profile they have and their needs. We have established very important strategies that help newspaper companies of this city to increase sales and attracting more customers, this will allow them to growth and economic power to such companies and remain in the market as pioneers in sales. Technological progress is very relevant in this investigation because the print media have been forced to create social pages where actualized and immediate information is disseminated, in order to maintain some way the customer satisfied and true to the brand. These pages must be constantly updated. The feasibility of this project, as results have good opportunities for companies in the print media (newspapers) on the market to which they are addressed, increasing productivity, labor and innovating the final product.